Vídeos educativos y su influencia en el aprendizaje de Lengua y Literatura del sexto grado, Unidad Educativa Padre Julián Lorente, Loja 2022-2023 - Lara Suárez, Dayana Alexandra (2023)
This present research work is related to educational videos and their influence on the learning of the students in sixth grade in the subject of Language and Literature, Unidad Educativa Padre Julián Lorente, Loja during the 2022-2023 school year, it was conducted with the following general objective: To determine the influence of educational videos on the learning of the students in sixth grade in the subject of Language and Literature of the Unidad Educativa Padre Julián Lorente. The methods used for the elaboration of this research work were: scientific, analytical, synthetic, hypothetical-deductive, statistical and bibliographical, which were used to effectively achieve the proposed goal. Techniques and instruments were used in the interview given to the teacher and a survey applied to the students, the actors who took part in the research work were 28 human resources, distributed in 27 students and 1 teacher, with the purpose of solving the investigated problem, it was determined that the educational videos influence the learning of the students in a positive way, they helped me to transmit knowledge through images, sounds, and the words that they express, stimulating the senses of the students and thus elevating their concentration which result in a better learning of the same; before which it was concluded that educational videos are didactic resources that help to a better transmission of conceptual contents facilitating the understanding of them in a way that captivates the interest of the students and motivates them to learn, optimizing time and allowing them to the development of activities, which is why very important to choose appropriately the videos to be used in order to obtain a better teaching. Key words: educational videos, learning, Language and Literature, methods, techniques, human resources.